Watchdog or lapdog? The demand for critical journalism during the corona crisis - Skovsgaard, Morten; Andersen, Kim; Heiselberg, Lene (Politica, 2022)
The role as society’s watchdog is central to citizens’ expectations of journalism, but how is the demand for critical journalism during societal crises such as the corona pandemic? Based on three representative surveys, we examine how citizens’ demand for critical journalism developed through the corona crisis, and who particularly demanded this type of journalism. Our results show that the demand for critical journalism increased over time, and that it was especially the voters of the opposition parties who demanded it. However, this party loyalty is moderated by voters’ perceptions of the consequences of the crisis for the economy and healthcare, i.e., especially opposition voters who disagreed with the government’s handling of the crisis demanded more critical journalism.